An apparent hiatus in global warming?. (5th December 2013) - Trenberth, Kevin E.; Fasullo, John T.
Abstract Global warming first became evident beyond the bounds of natural variability in the 1970s, but increases in global mean surface temperatures have stalled in the 2000s. Increases in atmospheric greenhouse gases, notably carbon dioxide, create an energy imbalance at the top‐of‐atmosphere (TOA) even as the planet warms to adjust to this imbalance, which is estimated to be 0.5–1 W m−2 over the 2000s. Annual global fluctuations in TOA energy of up to 0.2 W m−2 occur from natural variations in clouds, aerosols, and changes in the Sun. At times of major volcanic eruptions the effects can be much larger. Yet global mean surface temperatures fluctuate much more than these can account for. An energy imbalance is manifested not just as surface atmospheric or ground warming but also as melting sea and land ice, and heating of the oceans. More than 90% of the heat goes into the oceans and, with melting land ice, causes sea level to rise. For the past decade, more than 30% of the heat has apparently penetrated below 700 m depth that is traceable to changes in surface winds mainly over the Pacific in association with a switch to a negative phase of the Pacific Decadal Oscillation (PDO) in 1999. Surface warming was much more in evidence during the 1976–1998 positive phase of the PDO, suggesting that natural decadal variability modulates the rate of change of global surface temperatures while sea‐level rise is more relentless. Global warming has not stopped; it is merely manifested in different ways.